Review of Chimbutane, Feliciano 2011. Rethinking bilingual education in postcolonial contexts. N. H. Hornberger and C. Baker ed Bristol, Buffalo, Toronto: multilingual matters. 183p. - (:unkn) unknown (My University, 2013)
Critical additions to Chimbutane's survey of language policy in Mozambique in respect of African languages: Frelimo's denial and the early assimilation period
Keywords: African Research